Transient Eddy Current NDT: theory, applications and research - Sophian, Ali (2018)
Transient eddy current NDT has received a great deal of attention from researchers in the past 30 years and more, and yet, new applications and techniques are still being proposed and reported till today. The talk starts with the introduction on transient eddy current. It then covers the various applications of the technique that have been reported by researchers in both academia and industry. State-of-the art research works in the topic have been presented. Transient eddy current NDT with its broad bandwith of frequencies offers vast opportunities for research and potential applications, as an answer to the more stringent safety regulations.